A multifunctional additive of scandium trifluoromethanesulfonate to achieve efficient inverted perovskite solar cells with a high fill factor of 83.80%. Issue 37 (17th September 2020) - Li, Shufang; Zhu, Linna; Kan, Zhipeng; Hua, Yong; Wu, Fei
Abstract : A multifunctional additive of scandium trifluoromethanesulfonate is introduced into a perovskite film to achieve efficient inverted perovskite solar cells with a high fill factor of 83.80%. Abstract : High-quality perovskite films are critical to realize efficient photovoltaic performances of perovskite solar cells (PSCs). An unprocessed perovskite film contains a high density of defects, which results in low film quality. In order to reduce the trap density and passivate non-radiative recombination centers of perovskite films, scandium trifluoromethanesulfonate (Sc(OTF)3 ) is introduced into the perovskite precursor solution as a multifunctional additive. The sulfonic group could coordinate with lead ions, thus reducing the perovskite crystallization process, and a high quality perovskite film with large grain size, high crystallinity and few defects is obtained. Meanwhile, the doping of the rare earth ion Sc 3+ in the perovskite precursor solution could lead to the interaction of Sc 3+ with the perovskite, thereby improving film morphology and prolonging the charge carrier lifetime. In addition, the strong hydrogen bonding interaction between Sc(OTF)3 and MA + could immobilize methylamine ions (MA + ), contributing to the improved stability of the perovskite film. As a result, inverted PSCs with Sc(OTF)3 at a low doping amount of 0.1 mg ml −1 show a remarkable efficiency of 20.63% along with an open circuit voltage ( V oc ) of 1134 mV, a short circuit current density ( J sc ) of 21.71 mA cm −2, and a high fill factor (FF) of 83.80%. So far, the FF of this system represents one of the highest results for inverted PSCs.